Management Of Pondok Pesantren Modern Perspective Of Amin Abdullah's Interconnected Entities Theory In Pondok Pesantren Modern Al-Amanah Al-Gontory - Surip Surip; Masyitoh Masyitoh; Herwina Bahar (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This research employs a descriptive qualitative approach to examine modern Islamic boarding school management through Amin Abdullah's Interconnected Entities Theory, aiming to address management problems with scientifically-based solutions to achieve comprehensive targets. The theory addresses issues stemming from reliance solely on leadership experience, such as educator competence imbalances, lack of vision, split personality, and neglected values, which are fundamental to shaping the school's vision, mission, goals, and activities. The study explores whether this theory can be a viable solution for the Al-Amanah Al-Gontory Islamic boarding school in South Tangerang and other similar institutions. The research concludes that Amin Abdullah's Interconnected Entities Theory is an effective framework for developing eligible management by targeting monotheism through good parenting (Hadharah an-nashi), enhancing teacher competence through quality education (Hadharah al-ilmi), and fostering social ethics through a balanced social and economic approach (Hadharah falsafiyah). Thus, improving human resource competency is key to achieving comprehensive management outcomes.